The Role of the Family in Overcoming Children's Anxiety Regarding the Sound of Rainwater After the Cold Lahar Disaster - adrianti, bulan; fitriani, wahidah; yeni, putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
A child's anxiety cannot be separated from the role of the family in it. After the cold lava disaster, many children experienced anxiety about the sound of rainwater which reminded them of the cold lava flood incident. The role of the family is very important in helping children overcome this anxiety. This research aims to explore how family support can reduce children's anxiety about the sound of rainwater after a disaster. The method used is qualitative with a case study approach, involving in-depth interviews with affected families. The research results show that emotional support from the family, such as providing a sense of security, listening to children's complaints, and providing calming explanations about the sound of rain, is very effective in reducing anxiety. Apart from that, joint activities such as playing and telling stories also help children feel more comfortable. Active family involvement in providing support has consistently been proven to restore children's emotional well-being. This research emphasizes the importance of the family's role in the psychological recovery process of children after a disaster, and provides recommendations for families and related parties in dealing with similar problems in the future.